Cenozoic mafic to intermediate volcanism at Lava Mountain and Spring Mountain, Upper Wind River Basin, Wyoming - Downey, Anna Catherine (Kansas State University, 2015)
The Upper Wind River Basin (UWRB) is located in north-central Wyoming, to the south of the Yellowstone National Park boundary and east of Jackson Hole. Both Lava Mountain and Spring Mountain are Quaternary volcanoes in the UWRB. Lava Mountain is a shield volcano composed of 26 separate lavas capped by a scoria cone. Spring Mountain is located about ~36 km east of Lava Mountain, north of Dubois, WY, where eruptions of basalt cut through Paleocene and Eocene strata. The goal of this study aims to reconstruct the petrogenesis of magmas erupted at both volcanoes using geochemical, petrographic, and isotopic analyses. Important local events in geologic history played a large role in the development of the UWRB. This includes a long history of ancient and Cenozoic subduction, regional extension, and also the migration of the North American plate over the Yellowstone hotspot. The few previous studies on Lava Mountain claim the rocks are mafic in composition, however this was based solely on reconnaissance geological mapping. Geochemical evidence presented in this thesis show Lava Mountain rocks range from basaltic andesite to dacite. Basaltic andesite and dacite are interstratified at the base until approximately 2774 m; the rest of the volcano is andesite. All Lava Mountain samples are largely aphanitic and crystal-poor. Conversely, at Spring Mountain, localized normal faulting controls the location of eruptions of olivine-rich basalt. Petrographic analysis for both Lava Mountain and Spring Mountain display a range of evidence for open system processes, including sieved and/or resorbed pyroxenes, olivines and feldspars, as well as xenocrysts that suggest an influence from crustal assimilation. A petrogenetic model is introduced that discusses how Lava Mountain magma production occurred via fractional crystallization of basalt to dacite, then magma mixing of basaltic andesite and dacite, coupled with small amounts of crustal assimilation, to form the locally erupted andesites. All samples, including Spring Mountain basalts, have ⁸⁷Sr/⁸⁶Sr isotopes of 0.70608 and 0.70751, with ¹⁴³Nd/¹⁴⁴Nd isotopes of 0.51149 and 0.51157 and εNd values of -18 to -22. Pb isotopes plot to the left of the Geochron and directly on to slightly above the Stacey-Kramers curve. Strontium, neodymium, and lead isotope data suggest that Spring Mountain basalts are melts of ancient (e.g., 2.8 Ga Beartooth province) lithospheric mantle. The high ⁸⁷Sr/⁸⁶Sr values and exceptionally low εNd values separate the UWRB rocks from both Yellowstone and Snake River Plain volcanics, and suggest they originated from a different magma source. Finally, thermal evidence suggests melting genesis for UWRB rocks may not be Yellowstone plume related; rather it is more likely linked to Cenozoic extension.
Keywords: Igneous petrology; Lava Mountain; Spring Mountain; Upper Wind River Basin; Wyoming volcanism; Petrology (0584)